Simulating the Effects of Supply and Demand Elasticities on Political-Economic Equilibrium - Bullock, David S. (World Bank, Washington, DC, 2017)
Wallace's (1962) pioneering study brought to agricultural economics a focus on the role of supply and demand elasticity's in determining the efficiency with which agricultural policy transfers income among interest groups. His discussion provides key insights into what I call the "consequences of policy" side of current models of political economy. Becker's (1983) and Grossman and Helpman's (1994) models, both famously seminal in the political economy literature, have such "consequences" sides, and therefore when agricultural policy is examined in their models' frameworks, market elasticity's play key roles. These two models have also "causes of policy" sides, which describe interest groups' abilities to create political pressure. Wallace aim is to provide a theoretical review and exposition of the effects of elasticity's on redistribution efficiency, and in turn on distortional policies in political economic equilibrium. He demonstrates how models of actual political economies might be built and used to derive theoretical predictions about how market elasticity's affect policy and income transfers. Applying similar models to examine real world political economies can provide testable hypotheses about how market parameters affect distortional policies.